2018
DOI: 10.1088/1367-2630/aadceb
|View full text |Cite
|
Sign up to set email alerts
|

Structural resilience of spatial networks with inter-links behaving as an external field

Abstract: Many real systems such as, roads, shipping routes, and infrastructure systems can be modeled based on spatially embedded networks. The inter-links between two distant spatial networks, such as those formed by transcontinental airline flights, play a crucial role in optimizing communication and transportation over such long distances. Still, little is known about how inter-links affect the structural resilience of such systems. Here, we develop a framework to study the structural resilience of interlinked spati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Hence, the system of three exponents \beta , \delta and \gamma has two degrees of freedom in G2-core percolation. This phenomenon echoes a recent discovery for giant component based metric in modular network resilience [8,10] for continuous phase transitions. As a comparison, we show in Figure 6 the estimates of \beta = 0.07, \delta = 87, and \gamma = 0.08 for G3-core percolation, which apparently do not satisfy the Widom identity.…”
Section: Qip (Qi)supporting
confidence: 80%
See 1 more Smart Citation
“…Hence, the system of three exponents \beta , \delta and \gamma has two degrees of freedom in G2-core percolation. This phenomenon echoes a recent discovery for giant component based metric in modular network resilience [8,10] for continuous phase transitions. As a comparison, we show in Figure 6 the estimates of \beta = 0.07, \delta = 87, and \gamma = 0.08 for G3-core percolation, which apparently do not satisfy the Widom identity.…”
Section: Qip (Qi)supporting
confidence: 80%
“…This is similar to the paradigm established in [1,20]; however, the introduction of community structure requires a nontrivial refined treatment of the probability partition to derive solvable self-consistency equations. It is tempting to consider a version of multivariate generating functions that have been used to deal with component based resilience in modular networks [30,8,10,33]. However, we find it cumbersome with a monolithic multivariate version and choose to track the interconnections separately from intraconnections in Gk-core percolation.…”
Section: Generating Function Formalismmentioning
confidence: 99%
“…According to the obtained results, stronger topological interdependence, in terms of either more dependency links (in full/partial interdependence) or lower tolerance (in tolerated interdependence) decreases the robustness of the multilayer network [31][32][37][38]42,[46][47]55,57]. In this regard, Fan et al [58] found the optimal fraction of interdependent nodes as r = 0.1. It suggests that if 10% of nodes have dependency links, the network is the most robust to random attacks.…”
Section: The Effect Of Topological/functional/dynamical Propertiesmentioning
confidence: 98%
“…Crucially, the size of the perturbation that a dynamical system on a network can tolerate, which is an operational definition of the network resilience [3], depends on the structure of the network. For example, a change in the network structure induced by the removal of a fraction of nodes and the associated edges may decrease the resilience of the system [29][30][31].…”
Section: Introductionmentioning
confidence: 99%